Ocus Treaty: Objectives and implications in the Indo-Pacific region - Ahmed, Professor. Alaa Jabbar (The International and Political Journal, 2022)
On September 15, 2021, the United States of America announced a new security alliance called (AUKUS) with the participation of Britain and Australia, under which the latter would obtain several nuclear-powered submarines. Thus, Australia becomes the seventh country in the world to own this type of submarine after America, Britain, France, the Russian Federation, China, and India. This agreement represented Australia’s retreat from the similar deal it had struck in 2016 with France. Therefore, this announcement sparked anger and protest in France at the government and media levels. This deal also revealed profound changes in the global strategic context and may contain contradictions in the positions of the countries of the Western world and their interrelationship.